Online Spelling Correction for Query Completion - Duan, Huizhong; Hsu, Bo-June (Paul) (WWW 2011, 2011)
In this paper, we study the problem of online spelling correction for query completions. Misspelling is a common phenomenon among search engines queries. In order to help users effectively express their information needs, mechanisms for automatically correcting misspelled queries are required. Online spelling correction aims to provide spell corrected completion suggestions as a query is incrementally entered. As latency is crucial to the utility of the suggestions, such an algorithm needs to be not only accurate, but also efficient. To tackle this problem, we propose and study a generative model for input queries, based on a noisy channel transformation of the intended queries. Utilizing spelling correction pairs, we train a Markov n-gram transformation model that captures user spelling behavior in an unsupervised fashion. To find the top spell-corrected completion suggestions in real-time, we adapt the A* search algorithm with various pruning heuristics to dynamically expand the search space efficiently. Evaluation of the proposed methods demonstrates a substantial increase in the effectiveness of online spelling correction over existing techniques.